Outage Performance of Free-Space OpticalCommunication Systems Over Turbulent Channels with Varying Atmospheric Visibilities - Rahat Ara; It Ee Lee; Zabih Ghassemlooy; Gwo Chin Chung; Muhammad Sheraz; Teong Chee Chuah (International Journal of Integrated Engineering, 2025)
Free space optics is the technology where beams of light provideoptical connection using a line-of-sight path for communication as aform of video, voice, and data information between two points. A fewof the FSO system's limitations include atmospheric attenuationcaused by weather, which is the most difficult issue to solve because itseriously impairs system performance and results in poor signaltransmission. One of the important performance measures foranalyzing and enhancing FSO functionality for various fading statesassociated with different data rates is outage probability. This articleexamines FSO in terms of transmission optical power, feasible bitrates, and outage probability under clear, hazy, and moderate toheavy rainy conditions. The MATLAB simulation is implemented to dothe performance study. However, aperture diameters D = {20, 40, 80,100} mm and link distances L = {2.0, 3.5, 5.0} mm are seen to beessential characteristics for evaluating system performance. For allscenarios, the system's power consumption can be minimized byusing larger aperture diameters at lower bit rates, particularly in clearweather.